2002
DOI: 10.1088/0029-5515/42/8/312
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of disruption generated runaways in JET

Abstract: Experiments have established the regions of parameter space in JET that lead to runaway generation in disruptions. Previous measurements on the structure of the runaway beam have been confirmed. The delay in runaway generation following temperature collapse is found to be caused by the very high density generated by the disruption. It is shown that runaway generation in JET can be best modelled and understood by including avalanche processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 8 publications
6
104
0
Order By: Relevance
“…As reported earlier from JET [4,8], runaway generation occurs only above a threshold for the toroidal magnetic field of about 2T (figure 1b). This threshold is also reported from Tore Supra [9], JT-60U [10] and TEXTOR (see below) and is thus independent from machine size.…”
Section: Runaway Electron Generationsupporting
confidence: 83%
See 3 more Smart Citations
“…As reported earlier from JET [4,8], runaway generation occurs only above a threshold for the toroidal magnetic field of about 2T (figure 1b). This threshold is also reported from Tore Supra [9], JT-60U [10] and TEXTOR (see below) and is thus independent from machine size.…”
Section: Runaway Electron Generationsupporting
confidence: 83%
“…More insight might be gained by measuring the energy spectrum of the runaways. with an earlier analysis, which showed that the maximum q 95 with runaway generation increases with B t and that the lower B t = 2 T limit coincides with q 95 = 2 [8].…”
Section: Runaway Electron Generationsupporting
confidence: 77%
See 2 more Smart Citations
“…6 In large scale tokamaks at the disruption moments production of runaway electrons and their second influences on plasma is very important. [7][8][9] Collision of intense runaway electrons with the first wall would significantly reduce the lifetime of the first wall in fusion reactors. Therefore control and annihilation of runaway currents for the future reactors have been considered by researchers and several methods such as plasma current ramping up, controlled inward plasma shifting, and safety factor decreasing, have been found in JT-60U.…”
Section: Introductionmentioning
confidence: 99%